1991
DOI: 10.1007/bf00273602
|View full text |Cite
|
Sign up to set email alerts
|

The POL1 gene from the fission yeast, Schizosaccharomyces pombe, shows conserved amino acid blocks specific for eukaryotic DNA polymerases alpha

Abstract: The POL1 gene of the fission yeast, Schizosaccharomyces pombe, was isolated using a POL1 gene probe from the budding yeast Saccharomyces cerevisiae, cloned and sequenced. This gene is unique and located on chromosome II. It includes a single 91 bp intron and is transcribed into a mRNA of about 4500 nucleotides. The predicted protein coded for by the S. pombe POL1 gene is 1405 amino acid long and its calculated molecular weight is about 160,000 daltons. This peptide contains seven amino acid blocks conserved am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…6 using TB19. This construct contains the N-terminal 190 amino acid residues of DNA polymerase a; TB19 contains putative NLSs (Table 3), but lacks the catalytic domain of the enzyme (Damagnez et al 1991). The intensity of nuclear¯uorescence in TB19 also showed characteristic changes during the mitotic and meiotic cell cycles.…”
Section: Live Observation Of Gfp-fusion Constructsmentioning
confidence: 99%
“…6 using TB19. This construct contains the N-terminal 190 amino acid residues of DNA polymerase a; TB19 contains putative NLSs (Table 3), but lacks the catalytic domain of the enzyme (Damagnez et al 1991). The intensity of nuclear¯uorescence in TB19 also showed characteristic changes during the mitotic and meiotic cell cycles.…”
Section: Live Observation Of Gfp-fusion Constructsmentioning
confidence: 99%
“…Peptide sequences of bovine p68 subunit were determined as described (Eckerskorn et al, 1988;Eckerskorn and Lottspeich, 1989) and the peptide FTLETLNSFEHEFLSK was used to synthesize two reverse complement, degenerate oligonucleotides p68 4k and p68 5k [p68 4k, 5 (Wong et al, 1988;Melov et al, 1992). Conserved regions of p180 are underlined and named with letters or Roman numerals above the amino acid sequences (Damagnez et al, 1991). The primers used for DNA amplification and the 5'-3' polarity are indicated by the arrows with the names underneath them.…”
Section: Cdna Cloning Of Dna-polymerase-a-primase Subunitsmentioning
confidence: 99%
“…The cDNAs encoding the subunits of DNA-polymerasea-primase from several eukaryotes have been cloned and sequenced; cDNAs for all four subunits from yeast and mouse, p180 DNA polymerase a and p73 subunit from Drosophila, human p180 DNA polymerase a and, recently, p68 (Lucchini et al, 1987;Pizzagalli et al, 1988;Wong et al, 1988;Foiani et al, 1989a;Prussak et al, 1989a;Brooke et al, 1991;Damagnez et al, 1991;Hirose et al, 1991;Cotterill et al, 1992;Melov et al, 1992;Collins et al, 1993;Miyazawa et al, 1993). Sequence comparisons showed that p180 DNA polymerase a is distantly related to DNA polymerases from bacteriophages, viruses and bacteria and contains several regions that are highly conserved among the mammalian, Drosophila and yeast p180 subunits (Braithwaite and Ito, 1993).…”
mentioning
confidence: 99%
“…ϩ , and pcn1 ϩ , encoding the catalytic subunits of Pol ␣, Pol ␦, Pol ε, and PCNA, respectively, have also been identified (12,14,23,46,61).…”
mentioning
confidence: 99%